Is there not a better way to prevent venousthromboembolism after total knee arthroplasty? - Snyder, Mark A.; Vyrva, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Background: aspirin at 325 mg twice daily is now included as a nationally approved venous thromboembolism prophylaxis protocol for low risk total knee arthroplasty patients. The purpose of this study is to examine if there is a difference in deep vein thrombosis occurrence after a limited tourniquet total knee arthroplasty using aspirin-based prophylaxis with or without extended use of mechanical compression device therapy. Methods: one hundred limited tourniquet total knee arthroplasty patients, whose deep vein thrombosis risk was managed with aspirin 325 mg twice daily for 3 weeks, were randomized to either utilizing an mechanical compression device during hospitalization only or extended use at home up to six weeks post-op. Lower extremity Duplex venous ultrasonography was completed on the second post-op day, 14 days post-op, and at 3 months post-op to confirm absence of deep vein thrombosis after treatment. Results: the deep vein thrombosis rate for the post-discharge mechanical compression device therapy group was 0 % and 23.1 % for the inpatient mechanical compression device group (p < 0.001). All deep vein thrombosis resolved by 3 months postop. Patient satisfaction was 9.56 ± 0.82 for post-discharge mechanical compression device patients versus 8.50 ± 1.46 for in patient mechanical compression device patients (p < 0.001). <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusion:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> limited tourniquet total knee arthroplasty patients that were mobilized early, managed with Aspirin for 3 weeks post-op, and mechanical compression device therapy for up to 6 weeks post-op experienced superior deep vein thrombosis prophylaxis than patients receiving mechanical compression device therapy only as an inpatient (p < 0.05). The 0 % incidence of non-symptomatic deep vein thrombosis prevented by Aspirin and extended use mechanical compression device further validates this type of prophylaxis in low deep vein thrombosis risk total knee arthroplasty patients.